2021
DOI: 10.3390/cancers13092140
|View full text |Cite
|
Sign up to set email alerts
|

Wound Fluid from Breast Cancer Patients Undergoing Intraoperative Radiotherapy Exhibits an Altered Cytokine Profile and Impairs Mesenchymal Stromal Cell Function

Abstract: Intraoperative radiotherapy (IORT) displays an increasingly used treatment option for early breast cancer. It exhibits non-inferiority concerning the risk of recurrence compared to conventional external irradiation (EBRT) in suitable patients with early breast cancer. Since most relapses occur in direct proximity of the former tumor site, the reduction of the risk of local recurrence effected by radiotherapy might partially be due to an alteration of the irradiated tumor bed’s micromilieu. Our aim was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…This long-term outcome is consistent with previous reports and prompts the hypothesis that a single large dose of radiation such as TARGIT-IORT given during the trauma of surgery might possibly have an abscopal effect, i.e., an effect away from the site of irradiation, by influencing the tumour microenvironment or by immunological mechanisms. 14 27 , 28 Strange as it may seem, such an abscopal effect appears to give long-term protection against deaths from cardiovascular causes and other cancers. The early separation of lines in the K–M curves that starts soon after randomisation also suggests such a ‘drug-like’ effect, while a separation starting a few years later in the comparison of TARGIT-IORT alone vs. EBRT suggests an effect of avoiding EBRT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This long-term outcome is consistent with previous reports and prompts the hypothesis that a single large dose of radiation such as TARGIT-IORT given during the trauma of surgery might possibly have an abscopal effect, i.e., an effect away from the site of irradiation, by influencing the tumour microenvironment or by immunological mechanisms. 14 27 , 28 Strange as it may seem, such an abscopal effect appears to give long-term protection against deaths from cardiovascular causes and other cancers. The early separation of lines in the K–M curves that starts soon after randomisation also suggests such a ‘drug-like’ effect, while a separation starting a few years later in the comparison of TARGIT-IORT alone vs. EBRT suggests an effect of avoiding EBRT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is no time for tumor repopulation. IORT immediately after the removal of the tumor modifies the cytokines like oncostatin-M, leptin and IL-1β in the wound fluids (38,39). Wound fluids from IORT-treated patients significantly inhibit mammary mesenchymal stromal cells proliferation in comparison to wound fluids of non-irradiated patients.…”
Section: Advantages and Disadvantages Of Iortmentioning
confidence: 99%
“…They found that several cytokines were overexpressed in the luminal A subtype in the IORT-treated group, which may have anti-tumor characteristics (111). In a recent study, Wuhrer et al analyzed seromas collected 24h after breast-conserving surgery (from 42 patients) with and without IORT treatment and observed dramatic changes in populations of immune cells and levels of cytokine (112). None of the investigated subpopulations, such as Treg, T cells, and myeloid cells, showed alteration in their activation states or their counts in cellular fraction analysis of the seroma and blood samples of the patients 24 h after IR treatment compared to control.…”
Section: Composition Of Breast Surgery-induced Seroma; Benign Maligna...mentioning
confidence: 99%
“…Moreover, analysis of MSCs-CM cultured in 0.5% IORT- and control-seroma and collected after 72h showed significantly decreased RANTES, GRO-α, and VEGF in the IORT-seroma group ( 112 ). To confirm the tumor inhibitory effects of IORT-seroma compared with non-IORT-seroma, we evaluated migration, proliferation, viability, and invasion in three BC cell lines.…”
Section: Introductionmentioning
confidence: 99%